Current developments in derivative actions under the Nigerian company law (2014)
This paper examines the process laid down by the Companies and Allied Matters Act (CAMA) 2004for bringing a Derivative Action by minority shareholders in Nigeria. The basis for the action is the exceptions to the rule in Foss v Harbottle and the need to ensure that fraudsters who are in control of the company’s machinery for filing action in the name of the company do not use the opportunity to enrich themselves to the detriment of the company. The procedure laid down in the CAMA as well as the restrictive interpretation of the law by the Supreme Court in Nigeria is analysed and the way forward suggested.